A zero-dimensional dryout heat flux model based on mechanistic interfacial friction models for two-phase flow regimes with channel flow in a packed bed. (October 2019) - Yeo, D.Y.; NO, H.C.
Highlights: Transition criterion for channel flow was developed in terms of void fraction and particle diameter. Mechanistic interfacial friction models were suggested based on two-phase flow regimes of a packed bed. A zero-dimensional dryout heat flux model was suggested using the suggested interfacial friction models. Predictions of the pressure drop and dryout heat flux were improved using the suggested models. Abstract: In this paper, two-phase drag models for a packed bed of uniform-size particles were suggested, and they were applied to the calculation of pressure drop and dryout heat flux. We provided physical basis for the two-phase flow regime model through the analysis of the interfacial friction ( Fi ). The suggested model provides flow patterns representing bubbly, slug, and channel flow and considering three criteria including d 2 Fi /d α 2  = 0, Fi  = maximum, and Fi  = 0. The results obtained from the three criteria were drawn with several observation-based experimental ones to generate the flow regime map (void fraction vs. particle diameter). Through the current flow regime map, we clearly saw the existence of channel flow in a packed bed with particles smaller than around 3.5 mm. Then, mechanistic interfacial friction models were developed on basis of the current two-phase flow map of bubbly flow, slug flow, channel flow and annular flow. The suggested interfacial friction models were validated with top- and bottom-flooding air-water experiments and boiling experiments. We found out that the capability of pressure drop estimation by the current model were significantly improved for a bed with small particles. Finally, a zero-dimensional dryout heat flux (DHF) model was derived using the suggested interfacial friction models, and validated against DHF experimental data for beds with 1-D configuration. The root-mean-square error (RMSE) of the suggested DHF model was 35%, which was the smallest among the RMSEs of the previous DHF models.